PEMETAAN POTENSI NAGARI ATAR BERBASIS PARTISIPATIF - Budiman, Novi; Irwandi, Irwandi; Maimori, Romi (JRCE (Journal of Research on Community Engagement), 2022)
Undang-undang No. 6 of 2014 has provided opportunities for each village to develop its potential for improving the welfare of the community. But there are still a few Village Governments who do not understand their potential. This has an impact on development programs designed by the village itself. This study aims to explore and map the potential possessed by Nagari Atar, both in physical and non-physical form. The method used in this study is CBR (Community Based Research). The data used in this study are primary and secondary data. Primary data obtained through questionnaires, interviews and observations. Secondary data obtained through document collection. The results showed that the Nagari Atar has the potential and social capital that can be developed for the welfare of the community, especially in agriculture, plantations, religion, education, tourism and immigrants.